The Landscape and Archaeology of Jebel Sabaloka and the Sixth Nile Cataract, Sudan - Lenka Suková; Václav Cílek (Interdisciplinaria Archaeologica)
There are only six cataracts on the Main Nile of which the sixth Nile cataract located ca. 80 km downstream of the confluence of the Blue and White Niles represents the southernmost and smallest of theseries. Despite its close vicinity to Khartoum, this area was the least studied cataract zone along the Middle Nile until 2009 when it became the object of geoarchaeological research by the Czech Institute of Egyptology (Faculty of Arts, Charles University in Prague) and the Institute of Geology (Academy of Sciences of the Czech Republic). Four field campaigns have been carried out in Jebel Sabaloka and the Sixth Nile Cataract up to now, of which the first two were focused on landscape archaeology of a “large scale”, i.e. on the recognition of all observable human influencesin the research area of approx. 15×20 km. The main result of the first landscape archaeological reconnaissance consistsin the localisation and first description of ca. 30 major sites spanning from the Middle Palaeolithic up to the recent past. A peculiar archaeological feature of this part of the nile Valley has turned out to be the existence of a dense network of terraced “villages” connected via old paths with the Nile and with the periphery of the mountains. Furthermore, two Christian and Islamic forts have been found at places guarding the crossing of the Nile above the sixth cataract. Last but not least, a large number of prehistoric sites, including an extraordinarily rich settlement dated to the Mesolithic and Neolithic periods, has been described as well. After the first two seasons, the findings of which are summarised in this paper, it can be argued that the last of the six Nile cataracts to be investigated has finally begun to reveal its rich and hitherto unknown archaeological past.